Black Robe - Beresford, Bruce, 1940-; Young, Aden.; LothaireBluteau; SandrineHolt (Canada Australia Alliance Communications Corporation, 1991)
In the 17th century a Jesuit priest and a young companion are escorted through the wilderness of Quebec by Algonquin Indians to find a distant mission in the dead of winter. The Jesuit experiences a spiritual journey while his young companion falls in love with the Algonquin chief's beautiful daughter underneath the imposing and magnificent mountains. Dread and death follows them upriver.
In the 17th century a Jesuit priest and a young companion are escorted through the wilderness of Quebec...
Brian Moore
Language(s): English Subtitle(s): French, Spanish
Keywords: Drama; History; Adventure